A Case of Anaphylaxis After the Ingestion of Yacon - Yun, Eun Young (The Korean Academy of Asthma, Allergy and Clinical Immunology; The Korean Academy of Pediatric Allergy and Respiratory Disease, 2010)
Anaphylaxis is a potentially life-threatening systemic allergic reaction, often with an explosive onset; the symptoms range from mild flushing to upper respiratory obstruction, with or without vascular collapse. Foods are common offending allergens and remain the leading cause of outpatient anaphylaxis in most surveys. Yacon (Smallanthus sonchifolius) is a plant native to the Andes region, where its root is cultivated and consumed mainly as food. Unlike most edible roots, yacon contains large amounts of ructooligosaccharides. Traditionally, yacon tubers have been used as a source of natural sweetener and syrup for people suffering from various disorders. We report the case of a 55-year-old woman who developed syncope and generalized urticaria after ingesting yacon roots. The patient had positive skin prick and intradermal tests to yacon extract. An open food challenge test was performed to confirm food anaphylaxis and was positive 10 minutes after the consumption of yacon roots. To our knowledge, this is the first reported case of anaphylaxis after the ingestion of yacon roots.